Are we on the same page? A review of horse training approaches, terminology use, and method reporting within the scientific literature - Bartlett, E.; Blackwell, E. J.; Cameron, L. J.; Hockenhull, J. (International Journal of Equine Science, 2024)
It is vital that the impact of different horse training approaches (TAs) is studied to ensure the methods employed are effective, ethical, and do not compromise equine welfare. While a range of TAs are referred to within the scientific literature, no research has explored whether the way these are applied, described, and reported is consistent across existing studies. This is problematic as differences in training application and method reporting may alter study outcomes, limit the potential for inter-study comparison, and impede effective scientific communication. A systematic search of the published literature from three online databases (Scopus, Web of Science, and PubMed) was used to identify studies that apply horse TAs within their methodology. A description of the training protocols was extracted from each paper and used to categorize the training approach(es) employed, identify their defining characteristics, and assess consistency within TA description. A total of 75 studies published between 1992 and 2021 were reviewed using a mapping review method, within which ten distinct TA categories were identified. Six of these aligned directly with the principles of learning theory; however, distinct differences in their application were identified. The four remaining categories were less clearly defined, with a wider range of terms used to describe them. Limited information provided within some methodologies would render accurate study replication impossible. This study highlights a need for more consistent and detailed reporting of horse TAs within the scientific literature, and subsequently, some initial recommendations to promote this have been made. This would facilitate communication between researchers and further enable comparisons to be made across studies, ultimately improving understanding of modern horse training practices and their welfare impact.